2012 IEEE/ACIS 11th International Conference on Computer and Information Science 2012
DOI: 10.1109/icis.2012.70
|View full text |Cite
|
Sign up to set email alerts
|

Mining Patterns with Domain Knowledge: A Case Study on Multi-language Data

Abstract: Multi-language data impairs the application of mining techniques in a generalized form, since language remains an impenetrable barrier. The advances on domain driven data mining and the study of its semantic aspects open a first window over it, in particular the D 2 PM framework [1].This paper proposes a new method for mining patterns over multi-language data, through the use of the D 2 FP-Growth algorithm and a language constraint, both defined in the context of the referred framework. The new constraint allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recent work (Antunes and Bebiano 2012) has demonstrated that constraints defined over ontologies may be used by constrained adaptations of the most-well known algorithms for pattern mining, namely apriori (Agrawal and Srikant 1994) and FP-growth (Han, Pei and Yin 2000), without impairing their efficiency, but enabling the reduction of the number of patterns discovered, focusing the discovery according to user expectations.…”
Section: Knowledge Explorationmentioning
confidence: 99%
“…Recent work (Antunes and Bebiano 2012) has demonstrated that constraints defined over ontologies may be used by constrained adaptations of the most-well known algorithms for pattern mining, namely apriori (Agrawal and Srikant 1994) and FP-growth (Han, Pei and Yin 2000), without impairing their efficiency, but enabling the reduction of the number of patterns discovered, focusing the discovery according to user expectations.…”
Section: Knowledge Explorationmentioning
confidence: 99%
“…The D 2 PM framework [15] has the goal of supporting the process of pattern mining with the use of domain knowledge, represented through a domain ontology, and encompasses the definition of pattern mining methods able to discover transactional and sequential patterns, guided by constraints. These constraints are the core of this framework, since they are the responsible for incorporating existing knowledge in the mining algorithm.…”
Section: Temporal Constraints and The D 2 Pm Frameworkmentioning
confidence: 99%